FUSD Board Candidate Jerry McMenamin and Friends Election Night at Mama Luz's - Watkins, Howard::::::::: (1989)
Luisa Medina pointing to early results: McMenamin 17.8%, Curry 24.1% and Gadebusch 22.5%; Measures A-1 and A-2 both passing